2021
DOI: 10.1097/md.0000000000028029
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration for patients with acute decompensated heart failure

Abstract: Background: Ultrafiltration plays an indispensable role in relieving congestion and fluid retention in patients with acute decompensated heart failure (ADHF) in recent years. So far, there is no consistent agreement about whether early ultrafiltration (UF) is a first-line treatment for patients with ADHF. We, therefore, conducted a meta-analysis to assess the efficacy and safety of UF. Methods: PubMed, Embase, and Cochrane Library databases were searched for randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(114 reference statements)
0
8
1
1
Order By: Relevance
“…Modulating ultrafiltration treatment parameters may further increase the superiority gap. A meta-analysis by Wang et al, 2021 recommends mean fluid removal to be set at ≥ 200 mL/h after their subgroup analysis demonstrated superior fluid removal, weight loss, and rehospitalisation rates [27]. We hypothesize that flow rate, which differs substantially between studies, may play a similar role in affecting cardiac and renal biomarkers.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Modulating ultrafiltration treatment parameters may further increase the superiority gap. A meta-analysis by Wang et al, 2021 recommends mean fluid removal to be set at ≥ 200 mL/h after their subgroup analysis demonstrated superior fluid removal, weight loss, and rehospitalisation rates [27]. We hypothesize that flow rate, which differs substantially between studies, may play a similar role in affecting cardiac and renal biomarkers.…”
Section: Discussionmentioning
confidence: 80%
“…Existing systematic reviews have concluded that ultrafiltration has a benign renal profile without including BUN within their outcomes [8,9,[25][26][27]. Although BUN was measured in five studies [3,5,7,10,16], it has not been sufficiently discussed within RCT manuscripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that patients in the early ultrafiltration group experienced greater weight reduction, a lower rate of re-hospitalization within 90 days, similar relief of dyspnea compared to the routine diuresis group, and a lower incidence of hypokalemia ( 11 ). Previous meta-analyses ( 22 ) have compared ultrafiltration with diuresis in patients with heart failure and have shown that ultrafiltration is more effective in reducing volume load and rehospitalization rate, but it does not reduce the incidence of adverse events and mortality. This study’s innovation lies in the timing of early ultrafiltration, which aims to determine the efficacy and safety of this approach in patients with acute decompensated heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although UF is more effective in fluid removal compared with diuretics and reduces readmissions due to HF, it is not possible to prove that UF is superior to diuretics because of adverse events and mortality in the UF group. Treatment outcomes seem to vary because of the multiple causes and different aetiologies of patients [ 75 ].…”
Section: Clinical Studiesmentioning
confidence: 99%